A case of lethal varicose vein rupture caused by massive leiomyoma. (November 2021) - Fassina, Giacomo; Rigato, Selene; Fassan, Matteo; Rotter, Gabriele; Sanavio, Matteo; Cecchetto, Giovanni; Viel, Guido
Highlights: A multi-disciplinary forensic approach is recommendable in any suspicious death. Death scene investigation (DSI) and blood pattern analysis (BPA) could be useful. Even a benign medical disorder can lead to death under some specific circumstances. Forensic autopsy with histology is recommendable in such cases. Abstract: Varicose veins are a common and benign disease, especially affecting the lower limbs of the elderly. This pathology can exhibit several complications, which in the majority of cases do not require medical treatment; life-threatening conditions are possible but extremely rare. We present here a suspected murder case in which a woman was found dead in her home with a large amount of blood soiling the floor and the furniture of her house. Death scene investigation (DSI) with body inspection and bloodstain pattern analysis (BPA) were not exhaustive in excluding a homicide, and the prosecutor asked for a forensic autopsy. During the dissection, a uterine neoplasia, which altered the lower limb venous system, was detected, thus allowing to reconstruct the physio-pathological mechanism of the formation and rupture of the varicose vein.